2010
DOI: 10.1002/macp.200900448
|View full text |Cite
|
Sign up to set email alerts
|

Poly(N,N‐dimethylacrylamide)‐block‐Poly(L‐lysine) Hybrid Block Copolymers: Synthesis and Aqueous Solution Characterization

Abstract: Four poly(N,N‐dimethylacrylamide)‐block‐poly(L‐lysine) (PDMAM‐block‐PLL) hybrid diblock copolymers and two PLL homo‐polypeptides are prepared via ROP of ε‐trifluoroacetyl‐L‐lysine N‐carboxyanhydride initiated by primary amino‐terminated PDMAM and n‐hexylamine respectively. The PLL blocks render the copolymers a multi‐responsive behavior in aqueous solution due to their conformational transitions from random coil to α‐helix with increasing pH, and from α‐helix to β‐sheet upon heating. The random coil‐to‐α‐helix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
(125 reference statements)
1
9
0
Order By: Relevance
“…Moreover, 3-armed and 6-armed diblock copolypeptides adopted comparable percentages of both coil and β -sheet/turn conformations. It demonstrated that PLL segments, due to their confinement, can adopt more ordered conformation by conjugating with a functional moiety on the side chain or a hydrophobic polypeptide on the chain end [ 38 , 39 , 40 , 41 , 42 ]. Rather, the PLL conformation exhibited little dependence on the conjugation of hydrophilic polymer on a PLL segment [ 16 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 3-armed and 6-armed diblock copolypeptides adopted comparable percentages of both coil and β -sheet/turn conformations. It demonstrated that PLL segments, due to their confinement, can adopt more ordered conformation by conjugating with a functional moiety on the side chain or a hydrophobic polypeptide on the chain end [ 38 , 39 , 40 , 41 , 42 ]. Rather, the PLL conformation exhibited little dependence on the conjugation of hydrophilic polymer on a PLL segment [ 16 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Harada et al and Triftaridou et al have reported that the conjugation of a polymer block on short PLL can facilitate the coil-to-helix transition with increasing pH and helix-to-sheet transition upon heating. 49,50 We have reported that the lysine block in the lysine-b-glycine block copolypeptide vesicles adopted predominantly b-sheet conformation at pH 11.2, which is due to the confinement of polypeptide chains in the assembled structures. 33 In this study, the results clearly showed that the hexanoyl substitution as well as the confined environment can facilitate PLH to undergo conformational transitions with the increase of pH.…”
Section: Discussionmentioning
confidence: 99%
“…As the pH increased from 4.68 to 7.4, the peak at 4.3 ppm corresponding to the alpha protons shifted slightly down field and the area of the peak decreased, indicating the formation of a helix conformation. 49,50 Further increasing the pH to 10.0 resulted in the disappearance of the peak corresponding to the alpha protons, as well as the significant decreases of the peak areas corresponding to the protons on the PLL side chain. It is attributed to the conformational transitions, consistent with the CD data.…”
Section: Nmr and Titration Analysismentioning
confidence: 99%
“…It has been previously reported that a short PLL chain conjugated with a polymer block can facilitate the coil-to-helix transition upon increasing pH and the helix-to-sheet transition upon heating. 42,43 We have reported that the connement of PLLbased block or gra copolypeptide chains in the assembled structures can facilitate the lysine segments to undergo conformational transition. 21,44,45 In this study, the results revealed that the alkyl chain substitution as well as the conned environment due to self-assembly can facilitate the gra copolypeptides to undergo conformational transitions.…”
Section: Chain Conformation Of Amphiphilic Copolypeptidesmentioning
confidence: 99%